Exploring the impact of political patronage networks on financial stability: Lebanon's 2019 economic crisis - Samar Abou Ltaif; Simona Mihai-Yiannaki (Economies, 2024)
Amid Lebanon's multifaceted economic crisis, this paper explores the intricate dynamics between political patronage networks and financial stability. Grounded in the theoretical frameworks of New Institutional Economics (NIE) and Project Management (PM), the study delves into how entrenched political elites and patronage networks have shaped Lebanon's financial system, exacerbating vulnerabilities and perpetuating the ongoing crisis. Utilizing qualitative methods including in-depth interviews, document analysis, and case studies, the research illuminates the pivotal role of political actors and their vested interests in economic policies and financial institutions. The findings reveal systemic governance failures, crony capitalism, and institutional decay as underlying causes of Lebanon's economic stress. In response, the paper proposes a comprehensive framework for governance reform that integrates insights from NIE and PM, emphasizing structured planning, accountability mechanisms, and institutional strengthening. The purpose of this study is not only to contribute to a nuanced understanding of Lebanon's challenges but also to offer actionable insights for policymakers, academics, and stakeholders to address the root causes of the crisis and pave the way for sustainable economic recovery and revitalization.
Keywords: 330; crony capitalism; governance; NIE; PM; political patronage networks